Cover and growth habit of Polylepis woodlands and shrublands in the mountains of central Argentina: human or environmental influence? - Renison, Daniel (2006)
Aim To determine whether the cover and growth habit of the main forest forming species (Polylepis australis BITT.) in a mountain range with low human population density is mainly affected by anthropogenic activities or by environmental influences. Location Central Argentina. Methods Using GIS and field surveys we established 146 plots of 30 × 30 m located in five river basins differing in human impact. We measured P. australis cover, growth habit of each individual (number of basal ramifications), index of long term human impact (percentage of rock exposed by soil erosion due to livestock and fires), evidence of logging, fire scars, local relief, percentage of rock outcrops and altitude above sea level. We analysed the influence of independent variables on P. australis cover and growth habit (average number of basal ramifications per plot) using correlations and General Linear Models. Results Polylepis australis cover was greater at intermediate altitudes above sea level and in areas with reduced long term human impact. Contrastingly local relief, percentage of rock outcrops and logging in the recent past did not have a major influence on P. australis abundance. Growth habit varied in complex patterns. Individuals with fewer ramifications were found in valley bottoms and more disturbed basins, while more ramifications were found at mid- and upper slopes and well preserved basins. In valley bottoms, ramifications decreased with increasing altitude whereas the opposite trend was observed for mid-slopes. Ramifications were positively related to fires in two river basins and in mid- and upper slopes but not in valley bottoms. Fire impact was always less in valley bottoms than at mid- and upper slopes. Main conclusions Human impact had a major role on P. australis cover, while growth habit was determined by complex combinations of potentially cumulative natural and anthropogenic factors. Even in sparsely populated mountains, both human impact and their interaction with natural environmental gradients influence plant communities and need to be understood for effective management.